Analisis Manajemen Risiko pada Usaha Laundry Rumahan: Studi Kasus Nadinda Laundry - Susi Nurohimah; Alma Aulia Siffa; Amira Muthi Ghassani; Fatimah Rahman; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study analyzes the risk-management practices at Nadinda Laundry, a home-based micro, small, and medium enterprise (MSME) laundry business in Bandung Regency, with the aim of identifying, analyzing, evaluating, and providing risk-treatment strategies to strengthen operational resilience. Using a qualitative exploratory approach through a case study, data were collected from semi-structured interviews with the owner, field observations, and secondary sources such as academic literature and government reports. The identification process revealed 30 risks classified into six categories: market, financial, marketing, operational, human resources, and legal. Risk analysis using a 5×5 likelihood and impact matrix showed high-level risks such as rising electricity prices (level 16), negative online reviews affecting reputation (12), machine breakdowns (12), and power outages (12), along with various medium- and low-level risks. Risk-treatment strategies include operational efficiency improvements, routine maintenance, supplier diversification, employee training, and regulatory compliance. The study concludes that systematic risk-management implementation can minimize risk impacts, enhance customer satisfaction, and support the sustainability of laundry MSMEs amid industry dynamics.